Association of High Serum Adiponectin Level With Adverse Cardiovascular Outcomes and Progression of Coronary Artery Calcification in Patients With Pre-dialysis Chronic Kidney Disease - Suh, Sang Heon; Oh, Tae Ryom; Choi, Hong Sang; Kim, Chang Seong; Lee, Joongyub; Oh, Yun Kyu; Jung, Ji Yong; Lee, Kyu-Beck; Oh, Kook-Hwan; Ma, Seong Kwon; Bae, Eun Hui; Kim, Soo Wan (Frontiers in Cardiovascular Medicine, 2022)
Background: Serum adiponectin level predicts cardiovascular (CV) outcomes and progression of coronary artery calcification (CAC) in general population, thought the association has not been validated in patients with chronic kidney disease (CKD). We here investigated the association of high serum adiponectin level with the risk of adverse CV outcomes and progression of CAC in patients with pre-dialysis CKD. Methods: A total of 1127 pre-dialysis CKD patients from a nation-wide prospective cohort of patients with pre-dialysis CKD in Korea were divided into the tertile by serum adiponectin level at the baseline. CV outcome of interest was fatal and non-fatal CV events and all-cause mortality. Progression of CAC was defined as coronary artery calcium score change more than 200 during 4-year follow-up. Results: Cox regression analysis revealed that high serum adiponectin is associated with increased risk of fatal and non-fatal CV events (adjusted hazard ratio 2.799, 95% confidence interval (CI) 1.348-5.811). In contrast, high serum adiponectin level was not significantly associated with all-cause mortality (adjusted hazard ratio 0.655, 95% CI 0.203-2.113). Binary logistic regression analysis revealed that high serum adiponectin level is also associated with increased risk of progression of CAC (adjusted odd ratio 2.078, 95% CI 1.014-4.260). Subgroup analyses demonstrated that the association of high serum adiponectin with increased risk of fatal and non-fatal CV events is not modified by age, gender, history of diabetes, estimated glomerular filtration rate, or spot urine albumin-to-creatinine ratio. Conclusions: High serum adiponectin level is associated with adverse CV outcomes and progression of CAC in patients with pre-dialysis CKD.